The impact of game addiction on social sensitivity and learning motivation - Sihono; Muhammad Haidar Hilmi; Putri Nadha Setyaningrum; Sintha Sih Dewanti (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2025)
This study examines the impact of game addiction on social sensitivity and learning motivation among first to fourth-semester students at UIN Sunan Kalijaga Yogyakarta. The goal is to understand the extent to which game addiction affects social interactions and academic motivation. The research method used is a quantitative approach with a case study design, utilizing online questionnaires administered to 52 respondents to collect data regarding their gaming behavior, social sensitivity, and academic motivation. The analysis results show a significant negative relationship between game addiction and social sensitivity (r = -0.388, p = 0.005), as well as between game addiction and learning motivation (r = -0.362, p = 0.008). The conclusion of this study is that game addiction has the potential to decrease students' social sensitivity and learning motivation. It is suggested that educational institutions develop effective intervention programmes to help students overcome game addiction, while also enhancing their social sensitivity and learning motivation.